Sand colic: A retrospective study of 6 cases - KARADIMA, V.; BILLI, T.; TYRNENOPOULOU, P.; DIAKAKIS, N. (Journal of the Hellenic Veterinary Medical Society, 2021)
Colic- loosely defined as abdominal pain- is very common in horses, with clinical signs ranging from mild to severe. More than ninety causes of colic have been described. When horses consume significant amounts of sand while eating, they may develop symptoms of sand colic. Sand accumulation in the gastrointestinal tract of horses can irritate the colonic mucosa (less likely gastric mucosa), leading, usually, to sand impaction. Six horses with sand colic were referred to the School of Veterinary Medicine of Aristotle University of Thessaloniki from 2014 to 2018. Age ranged from 7 years to 19 years. The horses were presented with a history of: mild to severe colic (6/6), anorexia (4/6), weight loss (3/6) and diarrhea (6/6). Gastrointestinal auscultation revealed a characteristic sound of “pouring sand” (4/6) while sand was found in the faeces in large quantities (6/6). In order to identify sand in the faeces, sand sedimentation test can be performed easily in the field. Rectal examination findings were: gassy dilation of the colon (2/6) and impacted segment of colon (4/6) with (2/6) or without (2/6) cecum tympany. These cases, depending on the severity of the symptoms, were treated either pharmaceutically (4/6) or surgically (2/6). Pharmaceutical treatment consisted of administration of fluids, NSAIDs, antibiotics and laxatives, with the later given via nasogastric tube. Psyllium and paraffin oil were selected as laxatives of choice in this study. Surgical treatment was elected in 2 horses due to failure of conservative treatment. One of the two horses, that underwent surgery, survived while the other developed postoperative peritonitis and died. Horses that were treated pharmaceutically, either showed improvement and survived to discharge (2/4) or did not survive due to poor response to treatment (2/4). Minimizing exposure to sand and dietary management were important in preventing recurrence of sand colic in all 3 cases. According to the authors’ knowledge, this is the first report of sand colic cases in Greece.